2016
DOI: 10.1007/s13277-016-5079-x
|View full text |Cite
|
Sign up to set email alerts
|

DUSP28 links regulation of Mucin 5B and Mucin 16 to migration and survival of AsPC-1 human pancreatic cancer cells

Abstract: The prognosis of pancreatic cancer has not improved despite considerable and continuous effort. Dual-specificity phosphatase 28 (DUSP28) is highly expressed in human pancreatic cancers and exerts critical effects. However, knowledge of its function in pancreatic cancers is extremely limited. Here, we demonstrate the peculiar role of DUSP28 in pancreatic cancers. Analysis using the Gene Expression Omnibus public microarray database indicated higher DUSP28, MUC1, MUC4, MUC5B, MUC16 and MUC20 messenger RNA (mRNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Our data suggest that MUC5B-AS1 acts as an oncogenic lncRNA that promotes cell migration by upregulating the expression of MUC5B in lung cancer. Previous studies have suggested that MUC5B could promote the cancer cell migration through the ERK1/2 signaling pathway 38 or Wnt/β-catenin signaling pathway 39 . Based on the fact that MUC5B-AS1 expression levels were highly positively correlated with MUC5B mRNA and exerted its function through MUC5B in lung cancer cells, we further verified the prognostic significance of MUC5B mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that MUC5B-AS1 acts as an oncogenic lncRNA that promotes cell migration by upregulating the expression of MUC5B in lung cancer. Previous studies have suggested that MUC5B could promote the cancer cell migration through the ERK1/2 signaling pathway 38 or Wnt/β-catenin signaling pathway 39 . Based on the fact that MUC5B-AS1 expression levels were highly positively correlated with MUC5B mRNA and exerted its function through MUC5B in lung cancer cells, we further verified the prognostic significance of MUC5B mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them, such as albumin (ALB) and apolipoprotein B-100 (APOB), have also been previously reported as more abundant in bile from PDAC patients [43]. Mucin 5B (MUC5B), a little-characterized secretory type of mucin previously found in human bile and overexpressed in PDAC tissues [22,72], was also selected. Interestingly, two other proteins identified in this analysis were the PC transporter ABCB4 (MCP3) and the angiotensin converting enzyme 2 (ACE2), both known to be upregulated in PDAC tissues [73,74].…”
Section: Application Of Machine-learning Methods To Bile Proteomic Damentioning
confidence: 99%
“…Herein, we provided the structural and biochemical data of DUSP28, which will serve as a basis not only for further researches aimed at unraveling the precise function and mechanism of action of DUSP28, but also for investigations of small molecules targeting this enzyme in the therapeutic approach. These works will be worthwhile because of recent reports indicating DUSP28’s involvement in hepatocellular and pancreatic cancers [ 16 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…DUSP28, also known as VHP, is a member of the subfamily of atypical DUSPs and contains a single catalytic domain, whose precise biological functions and enzymatic characteristics are largely unknown. Recent reports indicated that DUSP28 is implicated in hepatocellular carcinoma progression [ 16 ] and in migratory activity and drug resistance of pancreatic cancer cells [ 17 , 18 ], suggesting that this protein may be deeply involved in oncogenesis and could be a putative therapeutic target in some cancers. Although the crystal structure of mouse DUSP28 has been determined and deposited in the Protein Data Bank (PDB) as a result of a structural genomics study on protein phosphatases [ 19 ], neither structural nor biochemical analysis of DUSP28 accompanied that report.…”
Section: Introductionmentioning
confidence: 99%